Análise da resistência ao cisalhamento paralelo às fibras da madeira de acordo com a inclinação dos anéis de crescimento na seção transversal - Rodrigues, Edson Fernando Castanheira (Universidade Federal de São Carlos, 2022)
The shear strength parallel to the fibers (fv0) is quite important, so that it can be verified in the Ultimate Limit State (ULS) of connections (simple shear) and in bending and sheared beams (transverse shear). Wood is an orthotropic material, however the ABNT NBR 7190 (1997) standard does not consider any difference in fv0 changing the loading direction in terms of growth ring arrangements. So, this work assesses whether there is a statistical difference between the mean fv0 results when the load is applied in the tangential (Tan) and radial (Rad) directions of specimens’ cross-section of twelve species of the hardwood group. The findings are explained through the anatomy of these wood species. The protocols of ABNT NBR 7190 (1997) are considered to obtain fv0 in a plane tangential to the growth rings (240 tests) and in the radial orientation (240 tests) of the section, in addition to their characteristic values (fv0,k). Moreover, 240 samples were used in each test of moisture content, apparent density and compression parallel to the fibers. The latter is important to obtain the characteristic value (fc0,k) and classify mechanically the species, while the moisture content test and apparent density were essential because it is a hygroscopic material. Regarding the fv0 values, these were analyzed by means of analysis of variance (ANOVA) at a 5% significance level, while the Anderson Darling (AD) and multiple comparisons (MC) tests were performed for the ANOVA validation. Regarding the results found out, the apparent density values ranged from 437 Kg/m3 for Simarouba amara (Caixeta) to 1013.00 Kg/m3 for Peltogyne spp. (Roxinho), while the average compressive strength ranged from 32 MPa for Caixeta to 93.72 MPa for Hymenaea stilbocarpa (Jatobá). In relation to the mean parallel shear strength values, only the species of Hymenolobium petraeum (Angelim-pedra), Erisma uncinatum (Cambará-rosa) and Couratari sp. (Tauari) exhibited statistically different values when the load application plane was changed, reaching ratios between the tangential longitudinal (LT) and radial longitudinal (LR) planes (fv0,T/fv0,R) equal to: 0.50, 1.39 and 0.90, along with their ratios for characteristic values of 0.33, 1.65 and 0.85, respectively. Thus, it was identified that when the species exhibit thick fiber walls/thin lumen and abundance of axial parenchyma, the weakest strength direction was the parallel to its growth rings (Angelim-pedra and Tauari), on the other hand, when it presents fibers with thin walls/thick lumen, even exhibiting abundance of axial parenchyma, the lower strength direction turns to be the perpendicular/radial one (Cambará-rosa). It was also found that except for the species of Angelim-pedra, which presented in its tangential direction a characteristic shear strength parallel to the fibers (fv0,k) equivalent to 10% of the characteristic strength in parallel compression (fc0,k), the other species and directions analyzed never presented fv0,k less than 22% of the value of fc0,k, evidencing a conservative standard in prescribing that fv0,k/fc0,k is equal to 0.12 (12%) for all hardwood species. Lastly, it was identified a tendency of the brazilian standard to present considerably underestimated fv0 values in comparison to this and even other works, so that in the worst case, the Cambará-rosa species reaches a value of fv0 in its LT plane (fv0,T) equivalent to 238% of that determined by ABNT NBR 7190 (1997).
Analysis of the shear strength parallel to the wood fibers according to the slope of the growth rings in the cross-section
Keywords: Madeiras folhosas; Resistência ao cisalhamento paralelo às fibras; Direção tangencial e radial da seção; Espessura das fibras; Parênquima axial; Hardwoods; Shearing strength parallel to the fibers; Tangential and radial direction of the section; Fiber thickness; Axial parenchyma; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL; CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL::ANATOMIA VEGETAL; CIENCIAS BIOLOGICAS::MORFOLOGIA::HISTOLOGIA